FRUIT DAMAGES CAUSED BY BROWN MARMORATED STINK BUGS IN APPLES AND QUINCES - Attila Keseru; Flavia-Andreea Andrecan; Horia Alexandru Pop; Mihai Buta; Orsolya Borsai (Agricultura)
The brown marmorated stink bug (Halyomorpha halys), an invasive pest, poses a significant threat to fruit crops worldwide. This study investigates the nature and extent of H. halys injuries in apples (Malus domestica Borkh.) and quinces (Cydonia oblonga), focusing on the external and internal damage caused by their feeding behavior. In apples, external symptoms include sunken, discolored spots, while internal damage manifests as corking and tissue necrosis. Quince fruits displayed similar symptoms but were more severely affected, likely due to differences in texture and chemical composition. Feeding injuries also made both fruits more susceptible to secondary infections by pathogens, further reducing their marketability. These findings highlight the economic impact of H. halys on fruit production and emphasize the need for integrated pest management (IPM) strategies. Proposed measures include monitoring pest populations, deploying biological controls such as Trissolcus japonicus, and exploring RNA interference-based approaches to mitigate crop losses caused by this polyphagous pest.